Qualitative and quantitative composition of phytoplankton in the Golden Horn Bay, Japan Sea - I. V. Stonik (Известия ТИНРО)
Qualitative and quantitative composition of phytoplankton in the Golden Horn Bay (Japan Sea) was investigated in the period from October 2009 to October 2010. The water samples of 1 L volume were taken with Molchanov bottle at the 36th Berth where ship-repairing yards were located and naval and commercial ships were moored. The samples were fixed in Utermӧhl iodine solution and phytoplankton cells were concentrated by precipitation or by reverse filtration, then the concentrated samples were processed under microscope. In total, 135 species and intraspecific taxa of microalgae were detected, which belonged to 7 divisions. Average density of phytoplankton cells varied from 1.9 . 103 to 610.3 . 103 cells/L, its average biomass varied from 0.02 to 11.70 g/m3. Four peaks of the phytoplankton cells density were registered: in summer, spring, winter and fall (in descending order), with the highest density in June, but only one peak of the phytoplankton biomass was observed in February. The highest density (up to 1 . 106 cells/L) was formed by euglenophytes that was similar to the neighboring Amur Bay and obviously indicated organic pollution of the Golden Horn Bay waters. Comparing with results of previous observations in the 1990s and 2000s, the species diversity of dominant diatoms and euglenophytes has increased recently. These species are known as indicators of eutrophic waters and/or organic pollution.